Environmental Crimes and Their Consequences - Abdiqodirov Husnitdin Shokirovich; Qosimov Jurabek Sodiqovich; Boymirzaev Abdusattor Egamshukurovich (Zien Journals, 2022)
This article describes the environmental crimes that are currently leading to global consequences, their consequences and the measures to be taken in this area
Keywords: ecological education; ecological culture; ecological thinking; environmental crimes